The next Africa : an emerging continent becomes a global powerhouse - Bright, Jake; Hruby, Aubrey (2015)
"After decades of resting on the world's economic margins, Africa is in the midst of tectonic transformation, redefining itself as a source of innovation and a destination for capital investment"--
"The Next Africa will change the way people think about the continent. The old narrative of an Africa disconnected from the global economy, depicted by conflict or corruption, and heavily dependent on outside donors is fading. A wave of transformation driven by business, modernization, and a new cadre of remarkably talented Africans is thrusting the continent from the world's margins to the global mainstream. Finally, The Next Africa suggests a fresh framework for global citizens, public policy-makers, and CEOs to approach Africa. It will no longer be "The Hopeless Continent", nor will it become an overnight utopia. Bright and Hruby offer a more nuanced, net-sum, and data-rich approach to analyzing an increasingly complex continent, reconciling its continued challenges with rapid progress. The Next Africa describes a future of a more globally-connected Africa where its leaders and citizens wield significant economic, cultural, and political power--a future in which Americans will be more likely to own African stocks, work for companies doing business in Africa, buy African hits from iTunes, see Nigerian actors win Oscars, and learn new African names connected to tech moguls and billionaires"--
Part I Africa's Great Economic Leap: Why Global CEOs and the World's Smartest Business Thinkers are Talking about Africa -- Part II Constraints and Deal Breakers: A Brief Summary of Africa's post-cold war Disconnect from Global Markets (the Less Than 3 Percent Dilemma): Challenges That Could Derail the Opportunities of Africa's Historic Moment -- Part III Game Changers and Trailblazers: The Significant People, Places and Things Taking Africa into a New Era -- Part IV Africa Forward: A Look Ahead to a More Connected, complex, and Culturally Integrated Africa.
Includes index.
Includes bibliographical references and index.
Keywords: 2000-2099; Economic development -- Africa; BUSINESS & ECONOMICS -- International -- Economics; BUSINESS & ECONOMICS -- Knowledge Capital; Diplomatic relations; Economic development; Economic history; International economic relations; Africa -- Foreign economic relations; Africa -- Foreign relations; Africa -- Economic conditions -- 21st century; Africa